Was It Useful? Multilayered Outcome of a Psychosocial Intervention with Teachers in East Greenland - Glendøs, Mia (Outlines. Critical Practice Studies, 2016)
Multilayered outcomes were found in the results of a follow-up study for an action research project conducted in East Greenland. The project was based on a community psychology approach that stresses the interdependent relations of change, structure, people, and community and emphasized the fundamental issue of grounding an intervention in local utilization. The project focused on mobilizing the resilience of vulnerable schoolchildren by advocating the students’ perspectives in a collaborative intervention process with the teachers of a local school. The research question for the follow-up study was: What were the outcomes of the intervention project conducted with teachers of vulnerable students? In the intervention process, ideas for developing and changing practice were devised and articulated by the teachers themselves; however, implementation and change in practice did not happen linear to this process. The follow- up result of multilayered outcomes was analyzed in three main directional levels of implementation: a constructive externalization and implementation level, a generalized in-between level named forgetting-but-not-denying, and a resistance/rejection level (where no implementation occurred). The community psychology analysis and discussion of the results is supplemented with a cultural-historical theoretical dimension (primary from Jaan Valsiner) that focuses on individual processes of internalization and externalization and the different levels of integrating new knowledge. The paper summarizes crucial issues to consider in psychosocial intervention practice in order to implement change.